AN EFL TEACHER STRATEGY IN WRITING CLASS IN THE MIDST OF COVID-19 PANDEMIC - R. Bunga Febriani; Iskhak Iskhak; Yoksan Rizky Lesmana; Syafryadin Syafryadin (Lingua Scientia, 2023)
The aim of this research was to find out, how does the efl teacher encounter the Chinese students in her teaching free writing at English Course? The research conducted at Butterfly English Course in North Jakarta. The writer used Narrative inquiry to explored deep qualitative data. The participant is a female English course teacher who teach Chinese student at international class in an English Course. The instrument used was interview with semi structure interview to get a lot of data from her story and experience. The research found that using free writing helped the students to find and generate ideas easier in writing paragraph. Using mind mapping strategies which showed videos and image in prewriting stage can also make the student have more imagination and make them more enthusiastic in writing class. With a good approach and strategy, these methods get positive responses from the students and after doing this method, the results of student writing are better than before.    Keywords : narrative, assessment, imagination, improvement